Interaction of Gut Microbiota and High‐Sodium, Low‐Potassium Diet in Altering Plasma Triglyceride Profiles Revealed by Lipidomics Analysis. Issue 24 (28th November 2019) - Folz, Jacob; Oh, Young Taek; Blaženović, Ivana; Richey, Joyce; Fiehn, Oliver; Youn, Jang H.
Abstract : Scope: High sodium and low potassium (HNaLK) intake increases the risk of cardiovascular disease (CVD) and metabolic syndrome. The authors investigate if the dietary minerals interact with the gut microbiota to alter circulating lipid profiles, implicated in CVD and metabolic syndrome. Methods and results: Plasma samples from Wistar rats fed a control or HNaLK diet with or without antibiotic treatment ( n = 7 each, a total of 28) are subjected to lipidomics analysis. Lipidomic data are then analyzed using statistical and bioinformatics tools, which detect numerous lipid species altered by the treatments, and consistently demonstrated interactions between the gut microbiota and the HNaLK diet in altering circulating lipids, mainly triglycerides (TGs). Two distinct TG groups differentially regulated by antibiotic treatment are identified. One group (cluster 1), representing the majority of TG species detected, is downregulated, whereas the other group (cluster 2) is upregulated by antibiotic treatment. Interestingly, cluster 2 TGs are also regulated by the diet. Cluster 2 TGs exhibit greater carbon‐chain length and double‐bond content and include TGs composed of very‐long‐chain polyunsaturated fatty acids, associated with reduced diabetes risk. Conclusion: The HNaLK diet interacts with gut bacteria to alter plasma lipid profiles, which may be related to its health effects. Abstract : A high sodium and low potassium intake increase the risk of cardiovascular disease and metabolic syndrome. The authors investigate if the dietary minerals interact with the gut microbiota to alter circulating lipid profiles, which are associated with the risk of these diseases. The results suggest major roles of the gut microbiota and the dietary minerals in modulating plasma lipid profiles in the host.